2003
DOI: 10.1128/jcm.41.2.619-622.2003
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Patterns of Resistance to Fluconazole in Candida glabrata Isolates from a Patient with Oropharyngeal Candidiasis Receiving Head and Neck Radiation

Abstract: Candida glabrata has emerged in recent years as a significant cause of systemic fungal infection. We have previously reported on the first three patients receiving radiation for head and neck cancer to develop oropharyngeal candidiasis due to C. glabrata. The goal of this study was to track the development of increased fluconazole resistance in C. glabrata isolates and to evaluate previously described genetic mechanisms associated with this resistance from one of these three patients. The patient was a 52-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
78
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 21 publications
2
78
0
2
Order By: Relevance
“…has increased as a cause of BSI in U.S. intensive care units. Other studies have shown that in certain regions of the United States, C. glabrata both is a common cause of BSI and is also often resistant to fluconazole (26,30,35,42). The U.S. findings, however, may not be universal (15,24,27).…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…has increased as a cause of BSI in U.S. intensive care units. Other studies have shown that in certain regions of the United States, C. glabrata both is a common cause of BSI and is also often resistant to fluconazole (26,30,35,42). The U.S. findings, however, may not be universal (15,24,27).…”
Section: Resultsmentioning
confidence: 63%
“…There is no question that C. glabrata has emerged as an important, and potentially resistant, opportunistic fungal pathogen (9,10,26,30,35,40). Trick et al (40) have demonstrated that C. glabrata alone among Candida spp.…”
Section: Resultsmentioning
confidence: 99%
“…Often, these non-albicans species are associated with elevated MIC levels for the azoles, the most commonly prescribed class of antifungal drugs. It has been well documented that C. glabrata demonstrates both intrinsically low susceptibility to the azoles and the ability to develop frank resistance (8,12,13,14,15,16). Moreover, a recent increase in the trailing phenotype, with low-level resistance to the azoles, has been observed for the Candida tropicalis isolates (1, 3).…”
mentioning
confidence: 99%
“…In C. glabrata, upregulation of the ABC transporter genes CgCDR1 and CgCDR2 is primarily responsible for acquired azole resistance that remains stable over time (7,12). Increased expression of CgCDR1 and CgCDR2 upon fluconazole exposure has been observed in resistant C. glabrata clinical isolates (2,11,13) and in vitro (3). Treatment failures due to C. glabrata resistance to azoles have previously been described and occur mainly in AIDS patients with oropharyngeal candidiasis (2, 4, 6, 11).…”
Section: Case Reportmentioning
confidence: 99%
“…However, in only a few of these cases was genotyping performed to determine whether resistance was acquired and selected for in vivo. To assess this, both the original azole-susceptible isolates and the subsequent azole-resistant isolates must be genotyped to determine whether all isolates from the same patient were of the same strain (2,11).…”
Section: Case Reportmentioning
confidence: 99%